Effect of Dissolved Oxygen Concentration on the Microbiologically Influenced Corrosion of Q235 Carbon Steel by Halophilic Archaeon Natronorubrum tibetense - Qian, Hongchang; Ju, Pengfei; Zhang, Dawei; Ma, Lingwei; Hu, Yuting; Li, Ziyu; Huang, Luyao; Lou, Yuntian; Du, Cuiwei (Frontiers in Microbiology, 2019)
The influence of dissolved oxygen concentration (DOC) on the microbiologically influenced corrosion (MIC) of Q235 carbon steel in the culture medium of halophilic archaea Natronorubrum tibetense was investigated. The increase of DOC from 0.0 ppm to 3.0 ppm was found to strengthen the oxygen concentration cell by promoting cathodic reaction. Meanwhile, the increased DOC also promoted archaea cell growth, which could consume more metallic iron as energy source and aggravated the localized corrosion. When the DOC further increased to 5.0 ppm, the uniform corrosion was dominant as the biofilms became uniformly presented on the steel surface. Combined with the stronger inhibition effect of oxygen diffusion by the increased biofilm coverage, the MIC of carbon steel in the 5.0 ppm medium was weaker than that in the 3.0 ppm medium. From weight loss and electrochemical tests, the results all demonstrated that the carbon steel in the 3.0 ppm medium had the largest corrosion rate.